How does fire affect germination of grasses in the Cerrado? - Dairel, Mariana [UNESP]; Fidelis, Alessandra [UNESP] (Cambridge University Press (CUP), 2020)
Fire is a frequent disturbance in the Cerrado and is one of the major factors affecting vegetation structure and diversity. Fire events open gaps within the herbaceous layer and increase temperature fluctuation in the soil surface. In addition to being an important environmental filter for germination, fire is a germination cue for species with physiological dormancy. This study aimed to evaluate the germination of native grasses, using daily temperature fluctuations and heat shock to overcome physiological dormancy in native grasses. We also evaluated seed longevity after dispersal for some species. We conducted the daily temperature fluctuation experiments on seeds of ten native grass species, which were collected and then placed in germination chambers simulating thermal fluctuation throughout the day (19-55°C). We also subjected seeds to different heat-shock treatments: 100°C for 1 min, 100°C for 3 min and 200°C for 1 min. To determine seed longevity, we stored seeds for 6 and 12 months after collection and then set them to germinate (27°C, 12/12 h light). Non-germinated seeds from all experiments were tested for viability. Most species had low longevity and germination percentages. Those that had physiological dormancy were stimulated to germinate when exposed to temperature fluctuations. One species resisted temperatures up to 200°C. For all other species, neither treatment affected germination percentages. Our results indicate the importance of these environmental filters for seedling recruitment of these species, considering the low longevity and the presence of physiological dormancy.
Keywords: heat shock; native grass; physiological dormancy; seed germination; temperature fluctuation; tropical savannas